Public Toilets in the Feminine: Portuguese Female User Perspectives on Public Toilets and the International Movement Calling for Adoption of Gender Norms - Coelho, Bruna Isabel Alves (2021)
Dissertação de Mestrado em Antropologia Social e Cultural apresentada à Faculdade de Ciências e Tecnologia